Aplikasi Panduan Sholat Wajib dan Sholat Sunnah Berbasis Android - Petricia Oktavia; Muhamad Meky Frindo (Teknik Informatika Universitas Pamulang, 2020)
Technology has always been and will continue to develop, especially mobile based applications. Gadgets or devices become a media that becomes the choice to carry out useful processes such as education, in the era of all-round technology today or known as the millennial era. Not to be the main to students but to be fostered by the teacher, need guidance that will help from the beginning of the guide followed by a systematic evaluation process. Alpabeta Kindergarten is one of the kindergartens that have begun to implement prayer learning from an early age for students who are Muslim and have difficulty in implementation because the guidelines available in the form of books or applications are not accompanied by an evaluation process. The idea to design and build an Android-based application that can be an alternative solution in providing information on obligatory prayer and sunnah accompanied by a one-way evaluation process. This application serves as a media guide to obligatory and sunnah prayers and facilitate the community, especially students of Alpabeta Kindergarten for the learning process of obligatory prayers and sunnah prayers. The research method consists of 5 (five) stages including gathering needs, analyzing needs, designing applications, integrating and testing prototype forms, implementing prototype applications and evaluating. The results of testing the prototype application of the obligatory and sunnah prayer guides are as functional as expected. Evaluation of the application is also good with almost 99% presentation because all buttons on this application can run well and the application is easy to understand and easy to use by teachers and students of Kindergarten Alpabeta.